# Solve equation elimination method 8y-3x=5xy , 6y-5x=-2xy

1
by dkdk

2015-05-16T15:59:32+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
we eliminate the xy term.

8 y - 3 x = 5 x y          ---  equation  (1)

6 y - 5 x = - 2 x y            ---- equation (2)

multiply (1) by 2 and  multiply (2) with 5  and then add,

16 y - 6 x  +  30 y  - 25 x =  10 x y  - 10 x y
46 y - 31 x  = 0

so  y = 31/46 * x        --- (3)

substitute this value of y in  (1).

8 * 31/46 x  - 3 x  = 5 x * (31/46  x)

multiply by 46  and divide by  x  :

248  -  138  =  155 x
x  =  110 / 155 =  22/31
y = 31/46 * 22/31  = 11/23
=========================
another way:

Divide equations (1) and (2)  by xy:

8 / x  - 3 / y = 5         and      6 / x  - 5 / y = - 2

call 1/x = X  and  1/y  = Y

8 X - 3 Y = 5        --- (3)
6 X -  5 Y = -2        --- (4)

we eliminate X  by    (3)  * 3  -  (4) * 4

24 X  - 9 Y -  24 X  + 20 Y  =  15  + 8
11 Y = 23
=>  Y = 23 /11          =>  y = 11/23
substitute this in (3)

8 X  -  3 * 23 /11 = 5
8 X = 5 + 69/11  = 124/11
X = 31/22

=> x = 22/31

please click on thanks blue button above